Ameliorating acid infertile rice soil with organic residue from nitrogen fixing trees - Baggie, I.; Zapata, F.; Sanginga, N.; Danso, S. (2000)
Residues from two nitrogen fixing trees, Albizia zygia and Gliricidia sepium and one non nitrogen fixing tree Samania dinklagei and their combination with 50% of rice husk, were evaluated for their effect on growth and yield of rice (Oryza sativa) varieties (Rok 10 and Rok 23) grown in an Oxisol collected from a rice paddy in Inland valley swamps of Sierra Leone, West Africa. Ground and dried residues were mixed with soil and labelled with N15 ammonium sulfate (9.855% atom excess) at a rate of 10 mg N kg-1 soil. The 32P isotopic exchange method was used to determine the effect of organic residue incorporation on the bioavailable soil P status at five levels of P application. Albizia zygia and G. sepium had higher quality leaf litter (with relatively lower C/N, lignin/N and cellulose/N ratios) whereas Semania dinklagei and rice husk had high carbon, lignin and polyphenolic contents. Application of organic residue had positive effects on the soil available P status at varying degrees. Higher adsorption capacity, kinetic value and mean solution time of phosphates in solution were obtained with the A. zygia, and G. sepium residues. These values were lower with rice husk and S. dinklagei. Gliricidia sepium and A. zygia contributed more nitrogen derived from organic residue than rice husk and S. dinklagei but the mixture of A. zygia and G. sepium with rice husk enhanced N utilization.